Сучасні напрями розвитку підприємств у сфері туризму в Україні - Копець, Г. Р.; Кулиняк, І. Я.; Kopets, H.; Kulyniak, I. (Видавництво Львівської політехніки, 2020)
Досліджено сучасні напрями розвитку підприємств у сфері туризму, серед яких важливі врахування викликів нового тисячоліття, особливостей ресурсовикористання, впровадження електронного бізнесу в туризмі, інвестиційного та інноваційного менеджменту, сучасних концепцій менеджменту. Автори зробили спробу узагальнити сучасні умови розвитку туризму в Україні та фактори впливу на розвиток сучасних туристичних підприємств, обґрунтувати певні заходи, що повинно сприяти покращенню ситуації у сфері туризму. Проведені дослідження дали змогу запропонувати сучасні напрями та окремі заходи з розвитку підприємств у сфері туризму, які згруповано з позицій держави і регіонів, окремих туристичних організацій та споживачів туристичного продукту. Виокремлено результати впровадження запропонованих інструментів у діяльності підприємств у сфері туризму. Застосування запропонованих напрямів дасть змогу підвищити ефективність діяльності й показники роботи туристичних підприємств та всієї туристичної сфери України.

The modern areas of enterprise development in the tourist industry are considered in this article. Nowadays it is important to take into account the new challenges of the new millennium, features of resource use, implementation of e-business in tourism, investment and innovation management, modern management concepts. The authors attempted to summarize the factors influencing the modern tourism enterprises development, to substantiate certain conclusions, which should help improve the situation in tourism. Development of consciousness and psycho-emotional training of tourism workers and consumers of tourism services for the conservation of natural and recreational resources following the concept of sustainable development, ratified by Ukraine in the framework of international cooperation was considered. The effective work of tourism enterprises influences the successful development of Ukraine and its regions. The modern activity and development of enterprises in the tourist industry have been studied by the authors taking into account the latest theoretical approaches and modern management concepts. Successful work of tourism companies and organizations in the region will increase the efficiency of the entire tourist industry of Ukraine, individual performance indicators of enterprises, budget content in specific regions. Implementation of investment projects, innovative technologies, and modern management concepts will be able to contribute to the sustainable development of individual enterprises and regions, the successful activity of the Ukrainian tourist industry, and individual tourism companies and organizations following international agreements and conventions. Successful and profitable enterprises activity, due to the conscious, efficient staff work, involves rational resources use, which will increase the efficiency of tourism enterprises’ innovative activities. The basis for the implementation of new projects, e-business, effective resource management is an objective assessment, accurate analysis of the development level, and use of tourism enterprises resources, as well as the effectiveness of their activities. Ukrainian tourism enterprises (tourist entities and collective accommodation facilities) have the opportunity to increase tourist flows and annually improve their financial results from the provision of tourism services, confirming the status of Ukraine as a tourist attractive country in the global services market. Clustering and modern management measures application help to increase the level of tourism enterprises development. The article gives examples of efficient resource use, integrated management of tourism enterprises. Based on the conducted researches the modern directions and measures for tourism enterprises and staff development which will allow increasing the efficiency of tourism enterprises activity in Ukraine were suggested.
Modern directions of tourism enterprises development in Ukraine
Keywords: розвиток туристичних підприємств; інноваційний розвиток; ефективний менеджмент; інноваційний менеджмент; активність туристичних підприємств; сучасні концепції менеджменту; tourism enterprises development; innovative development; effective management; innovative management; activity of tourism enterprises; modern management concepts; Z3; 338.48